1989
DOI: 10.1002/jbt.2570040107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of verapamil on glycogenolysis and gluconeogenesis in the perfused rat liver

Abstract: In perfused livers from fed rats, rates of glucose production (glycogenolysis) were 133 +/- 12 mumol/g/hr. Infusion of 2 microM verapamil into these livers decreased the rates of glucose production significantly to 97 +/- 15 mumol/g/hr within 10 min. Conversely, rates of production of lactate plus pyruvate (glycolysis) of 64 +/- 6 mumol/g/hr were not significantly altered by verapamil (60 +/- 3 mumol/g/hr). When 50 microM verapamil was infused, however, rates of both glycogenolysis and glycolysis were diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Accordingly, it has been reported that the intracellular calcium concentration can increase gluconeogenesis (28) and glycogenolysis (29), and that infusion of a calcium channel blocker (verapamil) into the rat liver diminishes hepatic glucose production (30). The identification of the molecular mechanism of this effect is beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 85%
“…Accordingly, it has been reported that the intracellular calcium concentration can increase gluconeogenesis (28) and glycogenolysis (29), and that infusion of a calcium channel blocker (verapamil) into the rat liver diminishes hepatic glucose production (30). The identification of the molecular mechanism of this effect is beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 85%